Computer Based Instruction (CBI)-flipped classroom development in learning: The experts' validity - Sukardi Sukardi; Rizki Hardian Sakti (Graduate School, Universitas Negeri Yogyakarta, 2021)
Technology has reached a level where it is time for genuine education reforms that increase student content attainment by teaching lessons relevant to the 4.0 industrial revolution. Students who are generation Z prefer to use technology in learning because, in the digitalization era, students raised on new media technology are impatient if they only fill out worksheets and listen to lectures. However, based on the observation, many students are bored with instructional media implemented in learning that is not computer-based innovative, and creative media. Therefore, the CBE-Flipped classroom is a computer-based learning media solution relevant to the development of learning in the 4.0 industrial revolution. After developing the CBE-Flipped classroom, researchers need to know whether the CBE-flipped classroom is what is expected. Researchers also need a paradigm of whether they have developed a valid CBE-flipped classroom so that the CBE-flipped classroom can be applied effectively as an instructional media in the classroom during the learning process. So, this study aims at describing the expert validity of the CBE-Flipped classroom before implementation in the learning process. Based on the study results, it can be concluded that the media design has been valid in terms of didactic, construction, and technical aspects. While the results of material validation also indicated that the material on the media has been valid in terms of quality of content, learning, interaction, and appearance. It can be concluded that the CBE-Flipped classroom can be applied effectively as an instructional media in the classroom during the learning process.